The current trend of exosome in epithelial ovarian cancer studies: A bibliometric review - Baghban, Neda; Ullah, Mujib; Nabipour, Iraj (Frontiers in Pharmacology, 2023)
Background: Exosomes are of academic interest as new biomarkers, which reflect cell behavior in normal and pathological conditions such as epithelial ovarian cancer. Consequently, the current study aimed to investigate the research output of exosomes in epithelial ovarian cancer globally (EOC). Method: A bibliometric method was used for analyzing publications on exosome and epithelial ovarian cancer from the beginning to October 15th 2022 by searching keywords in Scopus, PubMed and Google scholar. Annual scientific publications, authors, citations, journals, co-authorships, and keywords co-occurrence were analyzed and plotted using Microsoft Office Excel and VOS viewer. 39 original journal articles and 3 reviews have been published since 2015 up to October 15th 2022. Results: The findings showed that China is the top country in research output, international collaborations, organization, author, and sponsorship. The top journals were the Journal of Ovarian Research, Oncotarget, and Tumor Biology, all in the United States. The top institution was Shanghai Jiao Tong University in China. The top author was Xipeng Wang. Co-occurrence analysis showed that academics’ interest is toward:1) 1) Exosomes as prognostic biomarkers of EOC as well as their role in the proliferation and migration of cells. 2) The role of exosomes in metastasis through different mechanisms; 3) The role of exosomes in epithelial-mesenchymal transition of ovarian cancer cells; 4) The diagnostic role of EVs in EOC; and 5) Conferring chemoresistance in EOC through the exosomal transfer of miRNAs. Conclusion: Research on the exosome and EOC has an increasing trend, and China is much more involved than other countries in research, financial support, and international cooperation. These findings could aid researchers to understand novel ideas and subjects interested by sponsors in this field.